P-024 Neurotuberculosis Secondary to Adalimumab. (February 2017) - Alexandre, Carlos; Rafael, Lages; Matheus, Azevedo; Luciane, Milani; Jane, Oba; Natália, Queiroz; Adérson, Damião; Adriana, Andrade
Abstract : Background: The introduction of anti-tumor necrosis factor alpha (anti-TNFα) agents has revolutionized the management of inflammatory bowel diseases. However, the immunomodulatory effect of these drugs is associated with an increased risk of infection, especially an increased risk of tuberculosis reactivation, which usually occurs in the early stage of treatment. Tumor necrosis factor is an important cytokine involved in the cytotoxic effect of macrophages against intracellular pathogens, granuloma formation, apoptosis and prevention of dissemination of infection to other sites. Neurotuberculosis is a rare presentation and is responsible for high morbidity and mortality. Its diagnosis is largely based on suspicious symptoms, and the prognosis is directly related to the stage of the disease at the beginning of treatment. Methods: We describe a case of neurotuberculosis in a patient with Crohn's disease 9 months after starting therapy with adalimumab. Results: A 56-year-old man with a 30-years history of stenotic and fistulizing small bowel Crohn's disease presented with one month history of fever, followed by progressive confusion, drowsiness and loss of balance. On admission in the emergency department, the patient required endotracheal intubation due to decreased level of consciousness. Cerebrospinal fluid (CSF) analysis showed high protein (342 mg/dL), low glucose (27 mg/dL), pleocytosis (145 white blood cells/mm 3 ) with predominance of lymphocytes (76%), a negative acid-fast bacilli test, a negative polymerase chain reaction (PCR) assay for tuberculosis and a positive culture for Mycobacterium tuberculosis. On the magnetic resonance image of the brain, it was noticed 3 small enhancing nodules in the cerebellum and leptomeningeal enhancement. Nine months before, he had previously undergone to an ileal resection due to subocclusive symptoms secondary to an enteroenteric fistula and an ileal stricture. He was taking azathioprine for 15 years and adalimumab for the past 9 months. Before starting anti-TNFα therapy, an appropriate screening for latent tuberculosis infection was performed, with the investigation resulting in a normal chest x-ray and a negative tuberculin skin test. Initial management consisted in immunosuppressive therapy withdrawal and antituberculous treatment with rifampicin, isoniazid, ethambutol and pyrazinamide, plus prednisone. As a complication of neurotuberculosis, the patient presented hydrocephalus with no necessity of drainage and hyponatremia secondary to syndrome of inappropriate antidiuretic hormone. After 2 weeks of treatment, the patient was discharged from intensive care unit, evolving with progressive neurological improvement. Currently, 8 months after diagnosis, he maintains a mild cognitive deficit and requires some assistance with activities of daily living. Conclusions: The screening tests for tuberculosis before initiation of anti-TNFα therapy can miss latent infection, especially in immunosuppressed patients. We should always keep in mind the possibility of tuberculosis diagnosis in patients on anti-TNFα therapy presenting with fever of unknown origin.